Rethinking Environmental Consciousness: A Multimodal Peer-to-Peer Approach for Sustainable Behavioural Intention Change - Ding Hooi Ting; Tomomi Sudo; Hayato Hasegawa; Keitaro Ito (Australian Journal of Environmental Education)
Our study aims to (1) understand the impact of student-led knowledge dissemination and (2) examine the effects of multimodal interventions — comprising (i) a video on environmental catastrophes, (ii) pictorial reading materials on environmental issues (iii) lab-based simulated eco-tourism trips. This study involved students enrolled in a subject offered at Universiti Teknologi PETRONAS, Malaysia, attended by undergraduates from three different degree programmes. These interventions were implemented to examine their impact on both student advocates and their peers, particularly in terms of raising environmental awareness, shaping attitudes and fostering sustainable behavioural intentions (SBI). We equip students to become environmental advocates by providing them with environmental knowledge in class and assessing their ability to effectively share this knowledge with their peers. We conducted an experimental study using a multimodality intervention approach to assess changes in SBI. Study 1 measures the initial SBI without treatment, while Study 2 measures the incremental SBI after treatment. In our experiment, we requested 124 students (advocates) to reach out to at least three friends, and from this outreach, we obtained 401 respondents altogether. Our approach uncovers the effectiveness of same-level knowledge transfer (students to peers), facilitating the spread of environmental knowledge within peer groups.